URGENSI PEMBENTUKAN LEMBAGA APPRAISAL HAK CIPTA MUSIK SEBAGAI PEMENUHAN KEPASTIAN HUKUM DALAM PEMBIAYAAN JAMINAN FIDUSIA - Randhy, Muhammad; Gultom, Elfrida Ratnawati; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Fiduciary guarantee financing has penetrated into the world of music. However, in terms of the implementation of fiduciary jaminn financing through music copyrights, there are still problems related to the role of the appraiser as a determinant of the valuation of music copyrights. It becomes a further problem because the current legal aturn has not clearly regulated who and how the role of the music copyright appraiser so as to cause legal uncertainty in the implementation of the financing scheme. This research is a normative research that uses secondary data in its implementation. The secondary data consists of primary, secondary, and tertiary legal materials obtained through literature study. After the data is collected, it will be processed with qualitative data processing methods. The results showed that a special appraisal institution for music copyright is needed to improve the accuracy and objectivity of valuation, which has not been fully done by public appraisers. This institution can support copyright-based financing that is more optimal and safe for financial institutions.Keywords: Music Copyright, Fiduciary Guarantee, Appraiser, Valuation